Association between the β-blocker use and patients with sepsis: a cohort study - Yang, Qilin; Kong, Tianyu; Bao, Ziping; Yang, Shanshan; Chen, Xiaohua; Zheng, Jiezhao; Xiong, Xuming; Wen, Deliang; Zhang, Zhenhui (Frontiers in Medicine, 2023)
Objective This study aimed to assess whether β-blockers are associated with mortality in patients with sepsis. Method We conducted a retrospective cohort study of patients with sepsis using the Medical Information Market for Intensive Care (MIMIC)-IV and the emergency intensive care unit (eICU) databases. The primary outcome was the in-hospital mortality rate. The propensity score matching (PSM) method was adopted to reduce confounder bias. Subgroup and sensitivity analyses were performed to test the stability of the conclusions. Results We included a total of 61,751 patients with sepsis, with an overall in-hospital mortality rate of 15.3% in MIMIC-IV and 13.6% in eICU. The inverse probability-weighting model showed that in-hospital mortality was significantly lower in the β-blockers group than in the non-β-blockers group [HR = 0.71, 95% CI: 0.66–0.75, p < 0.001 in MIMIC-IV, and HR = 0.48, 95% CI: 0.45–0.52, p < 0.001 in eICU]. In subgroups grouped according to sex, age, heart rate, APSIII, septic shock, and admission years, the results did not change. Conclusion β-blocker use is associated with lower in-hospital mortality in patients with sepsis, further randomized trials are required to confirm this association.